1998
DOI: 10.1007/s004270050207
|View full text |Cite
|
Sign up to set email alerts
|

The anterior-like cells in Dictyostelium are required for the elevation of the spores during culmination

Abstract: Shortly after initiation of Dictyostelium fruiting body formation, prespore cells begin to differentiate into non-motile spores. Although these cells lose their ability to move, they are, nevertheless, elevated to the tip of the stalk. Removal of the amoeboid anterior-like cells, located above the differentiating spores in the developing fruiting body, prevents further spore elevation although the stalk continues to elongate. Furthermore, replacement of the anterior-like cells with anterior-like cells from ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Prespore cells move to the top of the stalk [63,65] and, terminally differentiate into spores. At this stage, the spores are contained in a more compact structure, the sorus of the late culminant (DDANAT:0000061).…”
Section: Resultsmentioning
confidence: 99%
“…Prespore cells move to the top of the stalk [63,65] and, terminally differentiate into spores. At this stage, the spores are contained in a more compact structure, the sorus of the late culminant (DDANAT:0000061).…”
Section: Resultsmentioning
confidence: 99%
“…This then starts a stalk-forming process directed downward, resulting in the formation of the basal disc, stalling fusion and successive elongation of the stalk [119] (figures 1 and 9). It has been suggested that the spore mass is lifted up the stalk by the combined crawling action of the lower-and upper-cup cells [120]. There has been one detailed model of culmination based on the cellular Potts model that captures some of the essential elements [121,122], but many questions, especially the role of cellular and tissue mechanics in this process, remain unresolved.…”
Section: Culminationmentioning
confidence: 99%
“…The existence of two classes of upper cup cells, those that express rtaA and those that express ecmB , implies a possible functional heterogeneity. The only function thus far ascribed to the upper cup is as a cellular motor that elevates the spore head up the stalk (Sternfeld, 1998). It will be of interest to know whether PstU cells participate in this process.…”
Section: Discussionmentioning
confidence: 99%
“…The ALCs were originally identified by staining with vital dyes such as neutral red and significant advances in understanding their function has been made by marking them in this way, e.g. the demonstration that the upper cup behaves like a motor that lifts the spore head up the stalk (Sternfeld, 1998). However, for many purposes, markers of gene expression are preferable to vital dyes and they provide the evidence for multiple prestalk and ALC sub-types.…”
Section: Introductionmentioning
confidence: 99%